"Is it making any difference?" A qualitative study examining the treatment‐taking experiences of asymptomatic people living with HIV in the context of Treat‐all in Eswatini. Issue 1 (29th January 2019) - Horter, Shona; Wringe, Alison; Thabede, Zanele; Dlamini, Velibanti; Kerschberger, Bernhard; Pasipamire, Munyaradzi; Lukhele, Nomthandazo; Rusch, Barbara; Seeley, Janet
Abstract: Introduction: Treat‐all is being implemented in several African settings, in accordance with 2015 World Health Organisation guidelines. The factors known to undermine adherence to antiretroviral therapy (ART) may change in the context of Treat‐all, where people living with HIV (PLHIV) increasingly initiate ART at earlier, asymptomatic stages of disease, soon after diagnosis. This paper aimed to examine the asymptomatic PLHIV's experiences engaging with early ART initiation under the Treat‐all policy, including how they navigate treatment‐taking over the longer term. Methods: A longitudinal qualitative study was conducted within a Médecins Sans Frontières/Ministry of Health Treat‐all pilot in Shiselweni, southern Eswatini. The Treat‐all pilot began in October 2014, adopted into national policy in October 2016. Participants were recruited purposively to include newly diagnosed, clinically asymptomatic PLHIV with a range of treatment‐taking experiences, and healthcare workers (HCW) with various roles. This analysis drew upon a sub‐sample of 17 PLHIV who had been on ART for at least 12 months, with mean 20 months on ART at first interview, and who undertook three interviews each. Additionally, 20 HCWs were interviewed once. Interviews were conducted from August 2016 to September 2017. Data were analysed thematically using coding, drawing upon principles of grounded theory, and aided by Nvivo 11. Results: It was important for PLHIV to perceive the need for treatment, and to have evidence of its effectiveness to motivate their treatment‐taking, thereby supporting engagement with care. For some, coming to terms with a HIV diagnosis or re‐interpreting past illnesses as signs of HIV could point to the need for ART to prevent health deterioration and prolong life. However, others doubted the accuracy of an HIV diagnosis and the need for treatment in the absence of symptoms or signs of ill health, with some experimenting with treatment‐taking as a means of seeking evidence of their need for treatment and its effect. Viral load monitoring appeared important in offering a view of the effect of treatment on the level of the virus, thereby motivating continued treatment‐taking. Conclusions: These findings highlight the importance of PLHIV perceiving need for treatment and having evidence of the difference that ART is making to them for motivating treatment‐taking. Patient support should be adapted to address these concerns, and viral load monitoring made routinely available within Treat‐all care, with communication of suppressed results emphasized to patients.